SPOROTRICHOSIS IN FELINES: CASE REPORT - Luiz Pinto Lopes, José; Platz Boccia, Gustavo; César Silva Lopes, Luiz; da Silva, Mardonio (Journal of Interdisciplinary Debates, 2026)
Sporotrichosis is a usually subcutaneous mycotic disease with important zoonotic relevance in Brazil, mainly related to felines. It is highly prevalent in tropical and humid climates, and peripheral and deprived regions. Due to the considerable increase in the number of sick people and animals, the aim of this study is to report a case of feline sporotrichosis in the city of Guarulhos, São Paulo. A male feline, mixed breed, by name Renan, weighing 3.4 kg, uncastrated, presented ocular discharge, snoring and ulcerated lesions in the region of the eyes, thoracic limbs, and ears. In view of the clinical signs presented by the animal, cytopathological examinations, complete blood count and biochemistry were performed, with the result suggestive of sporotrichosis. In view of the results obtained, the drug of choice for the treatment of the animal was Itraconazol 50mg/kg, every 24 hours SID, during new recommendations. The association of clinical signs, animal history, and established treatment response contributed to the confirmation of infection by the fungus of the genus Sporothrix schenkii. As this is a zoonosis considered to be emerging, the early diagnosis of the disease is extremely important, and it should be included as a differential diagnosis in cases of the presence of ulcerative lesions in felines. Additionally, responsible ownership is extremely important to reduce the incidence of abandoned animals that can serve as reservoirs of the disease for other animals and humans.